2019
DOI: 10.1088/2057-1976/ab5145
|View full text |Cite
|
Sign up to set email alerts
|

A correntropy-based classifier for motor imagery brain-computer interfaces

Abstract: Objective. This work aims to present a deeper investigation of the classification performance achieved by a motor imagery (MI) EEG-based brain-computer interface (BCI) using functional connectivity (FC) measures as features. The analysis is performed for two different datasets and analytical setups, including an information-theoretic based FC estimator (correntropy). Approach. In the first setup, using data acquired by our group, correntropy was compared to Pearson and Spearman correlations for FC estimation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Hence, since the brain can be considered as a non-linear dynamic system [41], and since EEG exhibits important non-linear characteristics [42], we chose to use this measure for computing similarities between the recorded time series of each pair of electrodes. Moreover, a recent application of correntropy to study classification scenarios of hands MI tasks showed that this measure was able to capture the expected spatial patterns of MI, while also performing better in terms of classification, when compared to other types of correlation metrics (namely, Pearson and Spearman correlations) [43]. Furthermore, even though other nonlinear approaches have been proposed to deal with these issues in the EEG signal, correntropy can be directly applied to the recorded data and, thus, generally becomes simpler and easier to compute [44].…”
Section: Graphs Adjacency Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, since the brain can be considered as a non-linear dynamic system [41], and since EEG exhibits important non-linear characteristics [42], we chose to use this measure for computing similarities between the recorded time series of each pair of electrodes. Moreover, a recent application of correntropy to study classification scenarios of hands MI tasks showed that this measure was able to capture the expected spatial patterns of MI, while also performing better in terms of classification, when compared to other types of correlation metrics (namely, Pearson and Spearman correlations) [43]. Furthermore, even though other nonlinear approaches have been proposed to deal with these issues in the EEG signal, correntropy can be directly applied to the recorded data and, thus, generally becomes simpler and easier to compute [44].…”
Section: Graphs Adjacency Matricesmentioning
confidence: 99%
“…Consider the recorded EEG signals represented by X (w) (t) = {x 1 (t), x 2 (t), ..., x d (t)} (w) , with a total of d channels and N data points, for each sample t in time window w. Let us omit the indice w in the quantity X (w) (t), for notation simplicity, and define a correntropy matrix V w [τ] for a given lag τ as such [40,43]:…”
Section: Graphs Adjacency Matricesmentioning
confidence: 99%
“…The authors plan to enhance the Gaussian functional connectivity that was developed for feature extraction as future work, allowing a better understanding of their impact and interaction on BCI-related tasks. To identify potential non-learners, the efforts can be directed toward a twofold aim: to enhance the feature extraction by profiting from more elaborate methods for measuring multivariate similarity, like centered kernel alignment [58,59], and to explore the robust estimation approaches based on information metrics (like correntropy) for dealing better with the variability [55,60,61]. Besides, modeling the temporal-dependencies within each trail to compute the FC is an exciting research line.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to temporal filters, spatial filters extract the necessary spatial information associated with a motor-related task embedded in EEG signals. A common average reference (CAR) is a spatial filter that removes the common components from all channels, leaving channels with only channel specific signals [ 17 ]. This is done by removing the mean of all k channels from each channel : …”
Section: Architecture Of MI Based Bcimentioning
confidence: 99%
“…In graph based methods, the EEG data are represented through graph adjacency matrices that correspond to temporal correlations (correlation approaches used like Pearson or Correntropy) between different brain regions (electrodes). Features are extracted from this graph in terms of the graph node’s importance, such as centrality measure [ 17 ].…”
Section: Architecture Of MI Based Bcimentioning
confidence: 99%